Physico-morphological Characteristics of Semen Ejaculates in Vrindavani Crossbred Bulls - Gemeda, Amare Eshetu; Ghosh, Subrata Kumar; Patra, Manas Kumar; Gupta, Shashi Kant; Srivastava, Neeraj; Kujur, Anju (Animal Reproduction Update, 2022)
In crossbred cattle bulls, poor seminal quality and freezability are major constraints. The present study was conducted to determine semen quality parameters of Vrindavani crossbred bulls. In this study 130 semen samples were collected from five Vrindavani crossbred bulls. The volume, mass motility, concentration and individual progressive motility, viability and abnormality of spermatozoa were examined. Then ejaculates were categorized into four groups on the basis of spermatozoa concentration and individual progressive motility. The percentage of normozoospermia, asthenozoopsermia, oligozoospermia and oligoasthenozoospermia ejaculates were 44.62%, 29.23%, 11.54% and 14.61%, respectively. The overall mean of volume, mass motility, concentration of spermatozoa, individual progressive motility, viability and sperm abnormality in semen ejaculates of crossbred Vrindavani bulls were 4.64±0.63 mL, 2.48±0.09, 772.20±27.95 million/mL, 65.08±1.47%, 79.94±1.07% and 7.82±0.44%, respectively. Ejaculate mass motility, concentration, progressive motility and abnormality of spermatozoa varied significantly (p
Keywords: Bulls; crossbred; semen; spermatozoa; Vrindavani